Chlorine disinfection of drinking water assessed by flow cytometry: new insights - Cheswick, Ryan; Moore, Graeme; Nocker, Andreas; Hassard, Francis; Jefferson, Bruce; Jarvis, Peter (Elsevier, 2020)
The efficacy of chlorine disinfection was assessed for the first time over a range of disinfection conditions using flow cytometry (FCM) to provide new insights into disinfection processes. Inactivation was assessed for pure culture bacteria (Escherichia coli) and micro-organisms in real treated water from operational water treatment works (WTWs). A dose dependent increase in inactivation rate (k) was observed for both test matrices, with values of 0.03 to 0.26 and 0.32 to 3.14 L/mg min for the WTW bacteria and E. coli, respectively. After 2 min, E. coli was reduced by 2 log for all chlorine doses (0.12 to 1.00 mg/L). In the case of the WTW filtrate bacteria, after 2 min log reductions were between 0.54 and 1.14 with increasing chlorine concentration, reaching between 1.32 and 2.33 after 30 min. A decrease in disinfection efficacy was observed as temperature decreased from 19 to 5 °C for both microbial populations. With respect to chlorination at different pH (pH 6, 7, 8), membrane damage was more pronounced at higher pH. This was not consistent with the higher disinfection efficacy seen at lower pH. when culture based methods are used to assess bacterial reductions. This provides evidence that more understanding into the fundamental mechanisms of chlorine disinfection are required and that methodological alterations may be required (e.g. pH standardisation) to fully utilise FCM over the entire range of chlorination conditions observed in operational environments
Keywords: Escherichia coli; Disinfection; Chlorination; Bacteria; Flow cytometry; Drinking water